2018
DOI: 10.1021/acs.macromol.8b02278
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Adenine-Containing Block Copolymer

Abstract: Nucleobase-containing polymers have received great attention for their complementary multiple hydrogen bonding between nucleobases. However, their polymerization is difficult due to poor solubility in a solvent. In this study, we successfully synthesized adenine-containing block copolymers, poly­(9-(4-vinylbenzyl)­adenine)-block-polystyrene (PVBA-b-PS), using reversible addition–fragmentation chain transfer (RAFT) polymerization in polar solvents of dimethyl sulfoxide and N , N-dimethyl­formamide and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…VBA and VBT monomers were synthesized according to the literature. ,, Styrene (Aldrich Chem., ≥99%) was purified using vacuum distillation over calcium hydride and the inhibitor in styrene was removed by passing through an activated alumina oxide column. 2-Cyano-2-propyl benzodithioate (CPBdT, Aldrich Chem., 97%) as a chain transfer agent (CTA) was used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…VBA and VBT monomers were synthesized according to the literature. ,, Styrene (Aldrich Chem., ≥99%) was purified using vacuum distillation over calcium hydride and the inhibitor in styrene was removed by passing through an activated alumina oxide column. 2-Cyano-2-propyl benzodithioate (CPBdT, Aldrich Chem., 97%) as a chain transfer agent (CTA) was used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 Previously, we reported that with increasing the volume fraction of the PS block (f PS ) in PVBAb-PS, body-centered cubic spheres of PS, hexagonally packed (HEX) cylinders of PS, lamellae, and HEX cylinders of PVBA were formed. 21 Also, χ between PS and PVBA was high (0.5 at 200 °C) due to hydrophobic PS and hydrophilic PVBA. 21 However, to improve further the sensing and catalytic performance, a high-density array of nanopatterns consisting of nucleobase-containing blocks having a smaller feature size is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6, A). 33,34 Furthermore, multiblock amphiphilic copolymers were designed by the sequential RAFT polymerization of thymine acrylate, n-butyl acrylate, and Please do not adjust margins Please do not adjust margins adenine acrylate using a bifunctional macro-CTA agent (Fig. 6, B).…”
Section: B Nucleobase-containing Polymersmentioning
confidence: 99%